Space-surface bistatic synthetic aperture radar with navigation satellite transmissions： a review - Antoniou, Michail; Cherniakov, Mikhail; Ma, Hui (Science China. Information sciences, 2015)
This paper reviews the theory and practice of Space-Surface Bistatic Synthetic Aperture Radar （SS-BSAR） using navigation satellites as transmitters. In recent years, this innovative technology has reached a maturity stage which allows it to be considered for a wide range of applications. The paper covers the fundamental aspects of this technology as a radar system, such as the resolution, power budget and Point Spread Function （PSF） analysis, as well as its signal processing aspects and the state of the art in terms of advanced SAR techniques that it enables. Finally, the theoretical aspects of the paper may be directly transferred to the more generic SS-BSAR concept.